Citizenship, social and educational rights: Reflections for a pedagogy of human rights - Vila Merino, Eduardo Salvador; De Bringas, Asier Martínez (Education Policy Analysis Archives, 2010)
This article seeks to address human rights issues from a triple perspective. First, conceptually locating human rights in the context of globalization and making a critique of the liberal conception of human rights. Second, deepen citizenship as an element of visibility of the political and law and focus of education. Finally, think and bet on how the social and educational rights must become the guiding axes civil and political rights that they are not empty in practice. Definitively, it tries to articulate the central elements for a pedagogy of the human rights.